Improving the catalytic effect of peroxodisulfate and peroxodiphosphate electrochemically generated at diamond electrode by activation with light irradiation - de Araújo, Danyelle Medeiros; Sáez, Cristina; Cañizares, Pablo; Rodrigo, Manuel Andrés; Martínez-Huitle, Carlos A. [UNESP] (Elsevier, 2018)
Boron doped diamond (BDD) anode has been used to oxidatively remove Rhodamine B (RhB), as persistent organic pollutant, from synthetic wastewater by electrolysis, photoelectrolysis and chemical oxidation containing sulfate and phosphate as supporting electrolytes. RhB is effectively oxidized by electrolysis and by chemical oxidation with the oxidants separately produced by electrolyzing sulfate or phosphate solutions (peroxodisulfate and peroxodiphosphate, respectively). The results showed that light irradiation improved the electrolysis of RhB due to the activation of oxidants under irradiation at high current densities. Meanwhile, the efficiency of the chemical oxidation approach by ex situ electrochemical production of oxidants was not efficient to degrade RhB.
Keywords: Boron doped diamond; Electrolysis; Peroxosalts; Photoelectrolysis; Rhodamine B